Are dispersion corrections accurate outside equilibrium? A case study on benzene - Gould, Tim; Johnson, Erin R.; Tawfik, Sherif Abdulkader (Beilstein Journal of Organic Chemistry, 2018)
Modern approaches to modelling dispersion forces are becoming increasingly accurate, and can predict accurate binding distances and energies. However, it is possible that these successes reflect a fortuitous cancellation of errors at equilibrium. Thus, in this work we investigate whether a selection of modern dispersion methods agree with benchmark calculations across several potential-energy curves of the benzene dimer to determine if they are capable of describing forces and energies outside equilibrium. We find the exchange-hole dipole moment (XDM) model describes most cases with the highest overall agreement with reference data for energies and forces, with many-body dispersion (MBD) and its fractionally ionic (FI) variant performing essentially as well. Popular approaches, such as Grimme-D and van der Waals density functional approximations (vdW-DFAs) underperform on our tests. The meta-GGA M06-L is surprisingly good for a method without explicit dispersion corrections. Some problems with SCAN+rVV10 are uncovered and briefly discussed.
Keywords: benzene; DFT; dispersion; van der Waals

(untitled) - Grimme, S. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2011)

(untitled) - Dobson, J. F.; Gould, T. (J. Phys.: Condens. Matter, 2012)

(untitled) - Grimme, S.; Hansen, A.; Brandenburg, J. G.; Bannwarth, C. (Chem. Rev., 2016)

(untitled) - Woods, L. M.; Dalvit, D. A. R.; Tkatchenko, A.; Rodriguez-Lopez, P.; Rodriguez, A. W.; Podgornik, R. (Rev. Mod. Phys., 2016)

(untitled) - Hermann, J.; DiStasio, R. A., Jr; Tkatchenko, A. (Chem. Rev., 2017)

(untitled) - Klimeš, J.; Michaelides, A. (J. Chem. Phys., 2012)

(untitled) - Geim, A. K.; Grigorieva, I. V. (Nature, 2013)

(untitled) - Rösel, S.; Quanz, H.; Logemann, C.; Becker, J.; Mossou, E.; Cañadillas-Delgado, L.; Caldeweyher, E.; Grimme, S.; Schreiner, P. R. (J. Am. Chem. Soc., 2017)

(untitled) - Fabrizio, A.; Corminboeuf, C. (J. Phys. Chem. Lett., 2018)

(untitled) - Johnson, E. R.; Clarkin, O. J.; Dale, S. G.; DiLabio, G. A. (J. Phys. Chem. A, 2015)

Non-Covalent Interactions in Quantum Chemistry and Physics - Reimers, J. R.; Li, M.; Wan, D.; Gould, T.; Ford, M. J. (Elsevier, 2017)

Semiconductors and Semimetals - Gould, T.; Lebègue, S.; Björkman, T.; Dobson, J. F. (Elsevier, 2016)

Non-Covalent Interactions in Quantum Chemistry and Physics - Goerigk, L. (Elsevier, 2017)

Non-Covalent Interactions in Quantum Chemistry and Physics - Schröder, E.; Cooper, V. R.; Berland, K.; Lundqvist, B. I.; Hyldgaard, P.; Thonhauser, T. (Elsevier, 2017)

(untitled) - Grimme, S.; Ehrlich, S.; Goerigk, L. (J. Comput. Chem., 2011)

(untitled) - Goerigk, L.; Hansen, A.; Bauer, C.; Ehrlich, S.; Najibi, A.; Grimme, S. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Tawfik, S. A.; Gould, T.; Stampfl, C.; Ford, M. J. (Phys. Rev. Materials, 2018)

(untitled) - Řezáč, J.; Riley, K. E.; Hobza, P. (J. Chem. Theory Comput., 2011)

(untitled) - Goerigk, L.; Kruse, H.; Grimme, S. (ChemPhysChem, 2011)

(untitled) - Sinnokrot, M. O.; Sherrill, C. D. (J. Phys. Chem. A, 2004)

(untitled) - Takatani, T.; Hohenstein, E. G.; Malagoli, M.; Marshall, M. S.; Sherrill, C. D. (J. Chem. Phys., 2010)

(untitled) - Lejaeghere, K.; Bihlmayer, G.; Björkman, T.; Blaha, P.; Blügel, S.; Blum, V.; Caliste, D.; Castelli, I. E.; Clark, S. J.; Corso, A. D.; de Gironcoli, S.; Deutsch, T.; et al. (Science, 2016)

(untitled) - Hermann, J.; Alfè, D.; Tkatchenko, A. (Nat. Commun., 2017)

(untitled) - Sutton, C.; Risko, C.; Brédas, J.-L. (Chem. Mater., 2016)

(untitled) - Zang, L.; Che, Y.; Moore, J. S. (Acc. Chem. Res., 2008)

(untitled) - Neel, A. J.; Hilton, M. J.; Sigman, M. S.; Toste, F. D. (Nature, 2017)

(untitled) - Jurečka, P.; Šponer, J.; Černý, J.; Hobza, P. (Phys. Chem. Chem. Phys., 2006)

(untitled) - Lebègue, S.; Harl, J.; Gould, T.; Ángyán, J. G.; Kresse, G.; Dobson, J. F. (Phys. Rev. Lett., 2010)

(untitled) - Gould, T.; Gray, E.; Dobson, J. F. (Phys. Rev. B, 2009)

(untitled) - Gould, T.; Simpkins, K.; Dobson, J. F. (Phys. Rev. B, 2008)

(untitled) - Dobson, J. F.; Gould, T.; Vignale, G. (Phys. Rev. X, 2014)

(untitled) - Misquitta, A. J.; Spencer, J.; Stone, A. J.; Alavi, A. (Phys. Rev. B, 2010)

(untitled) - Dobson, J. F. (Int. J. Quantum Chem., 2014)

(untitled) - DiStasio, R. A., Jr; von Lilienfeld, O. A.; Tkatchenko, A. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Ambrosetti, A.; Ferri, N.; DiStasio, R. A., Jr; Tkatchenko, A. (Science, 2016)

(untitled) - Gobre, V. V.; Tkatchenko, A. (Nat. Commun., 2013)

(untitled) - Kim, K.; Jordan, K. D. (J. Phys. Chem., 1994)

(untitled) - Johnson, E. R. (J. Chem. Phys., 2011)

(untitled) - Maurer, R. J.; Ruiz, V. G.; Tkatchenko, A. (J. Chem. Phys., 2015)

(untitled) - Christian, M. S.; Otero-de-la-Roza, A.; Johnson, E. R. (J. Chem. Theory Comput., 2016)

(untitled) - Otero-de-la-Roza, A.; Johnson, E. R. (J. Chem. Phys., 2013)

(untitled) - Otero-de-la-Roza, A.; DiLabio, G. A.; Johnson, E. R. (J. Chem. Theory Comput., 2016)

(untitled) - Huang, Y.; Beran, G. J. O. (J. Chem. Phys., 2015)

(untitled) - Řezáč, J.; Huang, Y.; Hobza, P.; Beran, G. J. O. (J. Chem. Theory Comput., 2015)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Wu, Q.; Yang, W. (J. Chem. Phys., 2002)

(untitled) - Wu, X.; Vargas, M. C.; Nayak, S.; Lotrich, V.; Scoles, G. (J. Chem. Phys., 2001)

(untitled) - Grimme, S. (J. Comput. Chem., 2006)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Elstner, M.; Hobza, P.; Frauenheim, T.; Suhai, S.; Kaxiras, E. (J. Chem. Phys., 2001)

(untitled) - Becke, A. D.; Johnson, E. R. (J. Chem. Phys., 2007)

Non-Covalent Interactions in Quantum Chemistry and Physics - Johnson, E. R. (Elsevier, 2017)

(untitled) - Tkatchenko, A.; Scheffler, M. (Phys. Rev. Lett., 2009)

(untitled) - Tkatchenko, A.; DiStasio, R. A., Jr; Car, R.; Scheffler, M. (Phys. Rev. Lett., 2012)

(untitled) - Ambrosetti, A.; Reilly, A. M.; DiStasio, R. A., Jr; Tkatchenko, A. (J. Chem. Phys., 2014)

(untitled) - Gould, T.; Bučko, T. (J. Chem. Theory Comput., 2016)

(untitled) - Gould, T.; Lebègue, S.; Ángyán, J. G.; Bučko, T. (J. Chem. Theory Comput., 2016)

(untitled) - Dobson, J. F.; Dinte, B. P.; Wang, J.; Gould, T. (Aust. J. Phys., 2000)

(untitled) - Dion, M.; Rydberg, H.; Schröder, E.; Langreth, D. C.; Lundqvist, B. I. (Phys. Rev. Lett., 2004)

(untitled) - Vydrov, O. A.; Van Voorhis, T. (J. Chem. Phys., 2011)

(untitled) - Lee, K.; Murray, É. D.; Kong, L.; Lundqvist, B. I.; Langreth, D. C. (Phys. Rev. B, 2010)

(untitled) - Klimeš, J.; Bowler, D. R.; Michaelides, A. (J. Phys.: Condens. Matter, 2009)

(untitled) - Peng, H.; Yang, Z.-H.; Perdew, J. P.; Sun, J. (Phys. Rev. X, 2016)

(untitled) - Zhao, Y.; Truhlar, D. G. (Theor. Chem. Acc., 2008)

(untitled) - Sun, J.; Ruzsinszky, A.; Perdew, J. P. (Phys. Rev. Lett., 2015)

(untitled) - Pernal, K.; Podeszwa, R.; Patkowski, K.; Szalewicz, K. (Phys. Rev. Lett., 2009)

(untitled) - Hermann, J.; Tkatchenko, A. (J. Chem. Theory Comput., 2018)

(untitled) - Kresse, G.; Furthmüller, J. (Phys. Rev. B, 1996)

(untitled) - Kresse, G.; Joubert, D. (Phys. Rev. B, 1999)

(untitled) - Blochl, P. E. (Phys. Rev. B, 1994)

(untitled) - Bučko, T.; Lebègue, S.; Gould, T.; Ángyán, J. G. (J. Phys.: Condens. Matter, 2016)

(untitled) - Klimeš, J.; Bowler, D. R.; Michaelides, A. (Phys. Rev. B, 2011)

(untitled) - Román-Pérez, G.; Soler, J. M. (Phys. Rev. Lett., 2009)

(untitled) - Parrish, R. M.; Burns, L. A.; Smith, D. G. A.; Simmonett, A. C.; DePrince, A. E., III; Hohenstein, E. G.; Bozkaya, U.; Sokolov, A. Y.; Di Remigio, R.; Richard, R. M.; Gonthier, J. F.; James, A. M.; et al. (J. Chem. Theory Comput., 2017)

(untitled) - Leconte, N.; Jung, J.; Lebègue, S.; Gould, T. (Phys. Rev. B, 2017)

(untitled) - Johnson, E. R.; Becke, A. D.; Sherrill, C. D.; DiLabio, G. A. (J. Chem. Phys., 2009)